"English Fever" in China Has Reached a Watershed - Xiaoyang, Wang; Yangyang, Li (International Higher Education, 2014)
The recent Gaokao language subject reform in China-lowering the score of English, raising the score of Chinese-has aroused extensive debate in public. The time consuming, low efficiency, and test-oriented English learning and the overlooking of Chinese learning, the increasing importance of Chinese language are the main reasons to start the reform. The reform to some extent implies that "English fever" has reached a watershed in China.